Лингвистическое представление графов с помеченными вершинами - Сапунов, С.В.; Сенченко, А.С. (Доповіді НАН України, 2019)
В работе вводится лингвистическое представление Д-графов, у которых в окрестности каждой вершины все вершины имеют разные метки, определяющей парой множеств слов, первое из которых описывает циклы графа, а второе — все его висячие вершины. Предложена процедура, которая по заданной паре множеств либо строит соответствующий ей Д-граф, либо показывает, что по этой паре Д-граф построить невозможно. Найдены процедура построения минимальной (канонической) определяющей пары для графа и процедура преобразования произвольной определяющей пары графа к канонической. Полученные результаты являются распространением соответствующих задач теории автоматов на графы с помеченными вершинами и позволяют задействовать новые методы и алгоритмы для решения задач анализа графов с помеченными вершинами. У роботі введено лінгвістичне зображення Д-графів, у яких в околі кожної вершини всі вершини мають різні мітки, визначальною парою множин слів, перша з яких описує цикли графа, а друга — усі його висячі вершини. Запропоновано процедуру, яка за заданою парою множин або будує відповідний їй Д-граф, або показує, що за цією парою неможливо побудувати Д-граф. Знайдено процедуру побудови мінімальної (канонічної) визначальної пари для графа та процедуру перетворення довільної визначальної пари графа до канонічної. Одержані результати є розповсюдженням відповідних задач теорії автоматів на графи з поміченими вершинами та дозволяють використовувати нові методи та алгоритми для розв'язання задач аналізу графів з поміченими вершинами. The representation of deterministic graphs (D-graphs) by sets of words over the vertex labels alphabet is studied. A vertex-labeled graph is said to be a D-graph, if all vertices in the neighborhood of every its vertex have different labels. Vertex-labeled graphs are widely used in the modeling of various computational processes in programming, robotics, model checking, etc. In such models, graphs play the role of an information environment of single or several mobile agents. Walks of agents on a graph determine the sequence of vertices labels or words in the alphabet of labels. For D-graphs in case where the graph as a whole and the initial vertex (i.e. the vertex, from which the agent started walking) are known, there exists the one-to-one correspondence between the sequence of vertices visited by the agent and the trajectory of its walks on the graph. In the case where the D-graph is not known as a whole, the agent walks on it can be arranged in such way that an observer obtains information about the structure of the graph sufficient to solve the problems of graph recognizing, finding the op timal path between vertices, comparison between current graph and etalon graph, etc. In this paper, the linguistic representation of D-graphs by the defining pair of sets of words (the first describes cycles of the graph and the second — all its vertices of degree 1) is introduced. This representation is an analog of the system of defining re lations for everywhere defined automata. A procedure that either constructs a D-graph using a given pair of sets or shows that it is impossible to construct a D-graph from this pair is proposed. A procedure for constructing a minimal (canonical) defining pair for a graph and a procedure for converting an arbitrary defining pair of a graph to the canonical one are found. The obtained results are the extension of corresponding problems of the automata theory to vertex-labeled graphs. This representation allows us to use new methods and algorithms to solve the problems of analyzing vertex-labeled graphs.